(3JfHjg GdZGdWjf Ydi eZGdW GdeJhgejfs - (3fhQ GdOjf CHh YHO Gddg MejOGf Hf jMji Hf MejOGf GdbGSejs
(3ChdgG (B:s
(3CeG HYO MeO Pi GdYRI hGdWhd aEfi deG YQaJ WQakG ef CbhGd GdeNJdajf hHYVkG ef GUhd eZGdW GdeJcdajf hLedI ef QOhO GdCFeI GdgGOjf s
(3BNQgG (B:s
(3agPg LedI eG bUOJ Hg GdJfHjg ddeJYdejf Ydi WdH GdYde ef Cgdg heYOfg , hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs